PROTECTIVE EFFECT OF ASTAXANTHIN IN THE LUNG INJURY CAUSED BY ISCHEMIA REPERFUSION OF THE LOWER EXTREMITIES - H. T. Akkoyun; A. Uyar; A. Ş. Bengu; M. Bayramoglu Akkoyun; O.Arihan5and Ö.F. Keleş (Journal of Animal and Plant Sciences, 2019)
Pathological and biochemical alterations due to lower extremity (I/R) damage and protective effects of astaxanthine (AST) were investigated. Rats were divided into four groups. GI-Sham group (n=7):Anesthesia without (I/R)(2hours);GII-I/R (n=7) : 2 hours of ischemia and 2 hours of reperfusion under anesthesia; Group III-AST(n=7): Rats were subchronically orally administered for 7 days at 125 mg/kg astaxanthin (AST) and then anesthetized (2hours) without ischemia; GIV-I/R+AST (n=7) : 7 days prior to ischemia rats were subchronically orally administered 125 mg/kg astaxanthin (AST) and then 2 hours of ischemia and reperfusion under anesthesia; Then lung tissues were investigated for MDA,GSH and histopathology. An increase in MDA and a decrease in GSH was observed I/R administered group compared to control. Histopathological evaluations showed intense congestion in pulmonary veins and alveolar septum and partial alveolar macrophage and erythrocyte accumulation and edema was observed in lumens of some bronchioles and alveoli in the second and fourth group compared control.Second group (3.41) damage score had high significance compared to control (p≤0.001). Fourth group damage score (0.92) was indifferent from control but significantly different from I/R group (p≤0.001). As a result; The protective effect of AST has been demonstrated by biochemical, histopathological and immunohistochemical effects.
Keywords: Lung; Astaxanthin; Rat; MDA; GSH; Histopathology